Runx3, Brn3a and Isl1 interplay orchestrates the transcriptional program in the early stages of proprioceptive neuron development. - Kira Orlovsky; Elena Appel; Shay Hantisteanu; Tsviya Olender; Joseph Lotem; Ditsa Levanon; Yoram Groner (PLoS Genetics)
Background The development and diversification of sensory proprioceptive neurons, which reside in the dorsal root ganglia (DRG) and express the tropomyosin receptor kinase C (TrkC), depend on the transcription factor (TF) Runx3. Runx3-deficient mice develop severe limb ataxia due to TrkC neuron cell death. Two additional TFs Pou4f1 (also called Brn3a) and Isl1 also play an important role in sensory neuron development. Thus, we aimed to unravel the chromatin state of early-developing TrkC neurons and decipher the Runx3 high-confidence target genes (HCT) and the possible cooperation between Runx3, Brn3a and Isl1 in the regulation of these genes. Methods Runx3 expression is driven by the gene proximal P2 promoter. Transcriptome analysis was conducted by RNA-seq on RNA isolated from heterozygous (P2+/-) vs. homozygous (P2-/-) TrkC neurons and differentially expressed genes (DEGs) were determined. Genome-wide occupancy of Runx3, Brn3a, Isl1 and histone H3 acetylated on lysine 27 (H3K27Ac) was determined using CUT&RUN. The landscape of Transposase-accessible chromatin was analyzed via ATAC-seq. Findings The intersection of Runx3 genomic occupancy-associated genes and DEG data discovered 244 Runx3 HCT. Brn3a and Isl1 were found to bind to numerous genomic loci, some of which overlapped with Runx3. Most genomic regions bound by each of these three TFs or co-bound by them resided in distantly located enhancer regions rather than in gene promoters. In activated and suppressed neuronal Runx3 HCT, Runx3 cooperated mainly with Brn3a to regulate expression through distantly located enhancers. Interestingly, suppression of non-neuronal immune genes was mainly managed via Runx3 without Brn3a. The distribution of ATAC and H3K27Ac marked regions in Runx3 peaks containing at least one RUNX binding site (Runx3_RBS) revealed that while most promoter regions were marked by ATAC, a prominent fraction of intron/intergenic regions occupied by Runx3, Brn3a or Isl1 were unmarked by ATAC and/or H3K27Ac. Conclusions These analyses shed new light on the interplay of Runx3, Brn3a, Isl1, and open chromatin regions in regulating the Runx3 HCT in the early developmental stages of TrkC neurons.